Effect and safety of diluted vasopressin injection on bleeding during robot-assisted laparoscopic myomectomy: a protocol for a randomised controlled pilot trial - Eun Ji Lee; Hee Seung Kim; Ga Won Yim; Gwonhwa Song; Soo Jin Park; Yup Kim; Hyunji Lim; Seungmee Lee (BMJ Open, 2022)
Introduction Even though the injection of diluted vasopressin into the uterus is expected to reduce intraoperative bleeding with decreased adverse effects during robot-assisted laparoscopic myomectomy (RALM), there is a lack of relevant trials to show its effect and safety. Thus, this study was designed to compare the effect and safety of vasopressin injection on bleedings based on dilution levels of vasopressin with constant volumes during RALM.Methods and analysis This is a randomised controlled pilot trial, where a total of 39 patients will be randomly divided into three experimental groups in a 1:1:1 ratio. All patients will be classified into the three groups based on the dilution level of vasopressin: group 1—a solution prepared by mixing 20 units of vasopressin with 100 mL of normal saline to make a total of 100 mL; group 2—a solution prepared by mixing 20 units of vasopressin with 200 mL of normal saline to make a total of 100 mL and group 3—a solution prepared by mixing 20 units of vasopressin with 400 mL of normal saline to make a total of 100 mL. During RALM, we will inject diluted vasopressin at different concentrations with a total of 100 mL. As the primary endpoint, estimated blood loss would be compared. As secondary endpoints, we will check the level of haemoglobin and haematocrit, operation time, amount of transfusion, and the period of hospitalisation. In addition, we will check other complications related to vasopressin injection.Ethics and dissemination This pilot study has been approved by the Institutional Review Board of the Seoul National University Hospital (No. H-2011-107-1174). All potential subjects will be provided written informed consent. The results of this study will be published in peer-reviewed journals and be presented at academic conferences.Trial registration numbers NCT04874246 and CKCT0006225.